UJI POTENSI DAN MEKANISME ANTAGONIS BAKTERI ENDOFIT ASAL TUMBUHAN LIAR SEBAGAI AGENS HAYATI PENGENDALIAN Fusarium oxysporum SECARA IN-VITRO - RAHIMI, ANDI SITTI; KHAERUNI, ANDI; BANDE, LA ODE SANTIAJI; ARIYANTI, EKA LESTARI; SATRAH, VIT NERU; ASNIAH, ASNIAH (Jurnal Agroteknos, 2022)
This research motivated by the Fusarium oxysporum which is a soil borne fungus that can infect cultivated plants. F. oxysporum is a facultative parasite that is part of its life as a saprophyte and becomes a parasite if there is a host plant. This study aims to determine the potential of endophytic bacteria from wild plants as biological agents control of F. oxysporum in-vitro. This research was conducted at the Laboratory of Plant Protection, Phytophatology Unit, Faculty of Agriculture, Halu Oleo University from September 2020 to March 2021. The results showed that endophytic bacteria isolated from wild plants such as as Jamaica cherry/kersen (Muntingia calabura), Suruhan (Paperomia pellucida), and Markisa Hutan/Rambusa (Passiflora foetida) have the potential as biological agents to control F. oxysporum in vitro, with the two best isolates, namely ASR-7(3) and BK-3(2) which were to inhibit the growth of F. oxysporum through the mechanism of antibiosis and competition, produced enzyme bioactive compounds (amylase and protease) which degrade of pathogenic fungi, and are able to produce volatile compounds.